Grid impact and power quality assessment of wave energy parks: Different layouts and power penetrations using energy storage. Issue 8 (4th July 2021) - Parwal, Arvind; Hjalmarsson, Johannes; Potapenko, Tatiana; Anttila, Sara; Leijon, Jennifer; Kelly, James; Temiz, Irina; de Oliveira, Janaina Goncalves; Boström, Cecilia; Leijon, Mats
Abstract: Power fluctuations induced by wave energy converters (WECs) may reflect negative impact on the power quality of the power grid. Assessing their impact is an important step to ensure the grid compliance level of the energy park. The IEC 61000‐4‐15 standard classifies the allowable disturbances in the grid. This study analysed and assessed the grid impact in terms of flicker, harmonic distortion and voltage variations. The assessments were performed without energy storage and compared when using the energy storage. A single WEC is emulated as an irregular power output of a real WEC using a combined model of power take‐off in the Simulink model. Time series based on data obtained in earlier offshore experiments, conducted at the Lysekil research site in Sweden, is used to emulate a wave energy park (WEP) power in a land‐based test rig in real‐time power hardware‐in‐the‐loop simulations. A total of three and ten WECs are emulated by introducing a time delay in the time series to investigate the grid impact in each layout. Flicker emissions, voltage variations, individual and total harmonics of the voltage at the connection point in each layout are studied and compared with the limits to be grid compliant for layouts of the WEP. In addition, voltage and current harmonics for the single WEC and individual harmonics in each phase of the voltage are measured and analysed to assess the compliance level of the WEP.